OPTIMIZING THE ROLE OF WOMEN, CREATIVE INDUSTRY BASE ON LOCALITY, FIS UNJ, HIBAH BERSAING DIKTI, KEMENDIKBUD,2013. - Nadiroh Nadiroh; Uswatun Hasanah; Samadi Samadi (Program Pascasarjana Universitas Negeri Jakarta, 2016)
ABSTRACTThe low level of education has become a part of women's non dependent in economic. The purpose of this research is to get information about a woman‟s human resources potential; local natural resources potential which is able to be developed in creative industry; the need of guidance module; and the need of guidance program. The benefits of this research are: increasing the skill and expertise of women in forming and managing a creative industry base on locality; increasing a self-confidence to participate in creative industry base on locality, and increasing a gender equality and justice in participate on family.This research is using Research and Development method. In this research, there are 100 (a hundred) samples which are included: 30 (thirty) from Matraman, 30 (thirty) from Suku Dinas Perindustrian Jakarta Timur, 30 (thirty) from Desa Cipaok Citapean Bogor, and 10 (ten) from Bekasi.The conclusions of this research are: the guidance module is varies, it takes two weeks in guiding; a creative industry module in culinary, clothing, and entrepreneurship; the strategy of interactive dialogue and practice experience; systematical, and sustainable, Measured and standardized, with simulation and field visiting.Keywords: Guidance model, optimizing the role of women, creative industry base on locality